Jim and the beanstalk - Briggs, Raymond (New York : Scholastic Inc, 1970)
Jim climbs the beanstalk outside his window. He finds a giant at the top. This giant has problems. BIG PROBLEMS! Can Jim come up with a few BIG SOLUTIONS before he gets eaten?
Keywords: Beanstalk stories-Fiction; Giants stories-Fiction